Basic ecology of the Oaxacan Spiny-tailed Iguana Ctenosaura oaxacana (Squamata: Iguanidae), in Oaxaca, Mexico - Tamara Rioja; Arturo Carrillo-Reyes; Eduardo Espinoza-Medinilla; Sergio López-Mendoza (Revista de Biología Tropical, 2012)
The Oaxacan Spiny-tailed Iguana Ctenosaura oaxacana is a restricted species to the Isthmus of Tehuantepec in Southern Oaxaca, Mexico. This reptile is one of the less known iguanid species. We censustracked a population in the South of Niltepec, Oaxaca, Mexico from May 2010 to April 2011. Throughout one year, a total of 10 line transects were situated and recorded in the study area to determine relative abundance and density, and habitat type use (dry forest, Nanchal, grassland, riparian vegetation, and mangrove) by the species. This study reports a new C. oaxacana population on the Southeastern limit of species range. Although this species has a very restricted distribution and is in danger of extinction, C. oaxacana has a high population density when compared to other Ctenosaura species. A total of 108 individuals were recorded throughout the study. Dry forest (33.75ind/ha) and Nanchal (18.75ind/ha) were the habitats with higher densities. Comparisons between habitat types showed no significant differences between dry forest and Nanchal (W=15, p=0.0808). Results between seasons were similar. The Oaxacan Spiny tailed Iguana preferred first the dry forest, and then Nanchal, while avoided grassland, riparian vegetation, and mangroves. There was no difference in habitat use between males and females. Mean perch heights were 1.23±0.32 (n=30) in Nanchal, 2.11±0.30 (n=9) in grassland, 1.90±0.56 (n=54) in dry forest, 1.91±0.28 (n=9) in mangrove and 2.30±0.37 (n=6) in riparian vegetation. Species observed as refuge and perch were B. crassifolia (Nanchal); C. alata (grassland); Tabebuia sp., Genipa americana, G. sepium, Acacia sp., Ficus sp. and Haematoxylon sp. (dry forest); G. sepium, Acacia sp. and Guazuma ulmifolia (riparian vegetation); and C. erecta (mangrove). Live trees hollows and branches were used by species. Main threats to the species are excessive hunting and habitat loss. Furthermore, grassland fires are still common in the study area during the dry season, which can result in habitat loss and territorial displacement of individuals